Study on the Soil Corrosivity towards the Buried-Structures in Soil Environment of Tanglaphant-Tribhuvan University Campus-Balkhu Areas of Kirtipur - Gautam, M; Bhattarai, J (Nepal Journal of Science and Technology, 2014)
Soil parameters such as moisture, pH, resistivity, oxidation-reduction potential, chloride and sulfate ions were investigated, because these parameters affect the corrosive nature of soils toward the buried-galvanized steels and cast-iron pipelines used to supply drinking water in Tanglaphant-Tribhuvan University Campus-Balkhu areas of Kirtipur. The soil parameters examined in the study areas are found as: moisture (7-48%), pH (7.0-7.9), resistivity (6,300-37,000 ohm.cm), oxidation-reduction potential (307-490 mV vs SHE), chloride (13-92 ppm) and sulfate (62-309 ppm) contents. The results gave an indication of mildly corrosive to non-corrosive nature of soils on the buried galvanized steels and cast-iron pipes used to supply drinking water in the study areas of Kirtipur. DOI: http://dx.doi.org/10.3126/njst.v14i2.10417 Nepal Journal of Science and Technology Vol. 14, No. 2 (2013) 65-72